Aircraft - runway interaction and an insight into evolving civil aviation regulations - Yadav, Devinder Kumar (Curtin University, 2013)
Runway is an essential element of any airport and it significantly influences the safety of an aircraft that uses it. A typical flight includes various phases, but landing is considered as the most crucial phase of the flight. An improper landing may results in serious implications for safety of the aircraft and its occupants, if the runway condition is compromised. An aircraft imposes a tremendous load on a runway pavement during landing phase that causes deflection of the pavement. Consequently, the runway design and performance requirements are largely affected by the potential deflection. A critical review of the relevant literature indicates that the study of aircraft-runway interaction has been a challenging problem for runway designers, airport operators, and researchers. As a result, the design, evaluation, and performance reporting of a runway pavement is still based on semi-empirical approaches. A review of international civil aviation regulatory framework also reveals that prescriptive and empirical procedures dominate the field practices.This study analyses an aircraft-runway interaction as a structure-foundation interaction problem using basic principles of engineering mechanics. It is based on idealisation of various characteristics of a runway by mechanical elements, such as Winkler springs, stretched elastic membranes, shear beam, and dashpot concepts while considering the forces applied by an aircraft on a runway pavement during landing. As a result, an analytically derived deflection model has been developed to examine the runway deflection profiles. Besides, a parametric study has also been carried out to examine the relationship between deflection, impact pressure, and vertical velocity of an aircraft during landing. Consequently, the developed analytical expression to estimate runway deflection is expected to be useful in designing, technical evaluation, and strength reporting of a runway pavement. Additionally, considering aviation operations as risky and safety sensitive activities, the impact of changing civil aviation regulatory system from prescriptive regime to an outcome based legislative framework on aviation safety is also investigated in this research.